Pengaruh Cita rasa dan Kualitas Pelayanan terhadap Kepuasan Konsumen Gudeg Yu Djum Wijilan Yogyakarta - fitrotun nailah; Sri Utami, Kristiana (Transformasi: Journal of Economics and Business Management, 2024)
Finding out what makes Gudeg Yu Djum Wijilan Yogyakarta customers happy is the main goal of this study. Customer satisfaction (Y) is the dependent variable, whereas taste and service quality are the independent factors. One hundred Gudeg Yu Djum Wijilan Yogyakarta consumers who have bought and eaten this product make up the sample for this study. It is SPSS 25 that is utilized for the analysis. Research and analysis employing regression analysis led to the conclusion that High-Quality Taste and Service Significantly Impact Consumer Satisfaction.